Regional Variations of Slang in British English - Piddubna Veronika (My University, 2024)
This study is dedicated to slang as a linguistic phenomenon in British English. The work is intended to stress the importance of studying the varieties of English and nonstandard forms of the language. The paper consists of two parts: Part I, where the main features of slang are examined, and Part II, which analyses the representations of slang in modern British literature. The former discusses the definition and the characteristics of slang. As there has been much less research into it and due to its fluidity, slang remains one of the most ambiguous linguistic phenomena. Moreover, slang has often been deemed not worthy of the linguist’s attention as it represents a low layer of the lexicon and is usually represented by swear words and offensive or informal language. This work demonstrates that slang must be reconsidered and described from other perspectives. Despite its low language, slang is creative, playful, and non-conforming. Additionally, this paper tries to show that slang can represent regional differences in BrE, which are also part of the language. Apart from the definition and functions of slang, the theoretical part describes common types of word formation and semantic categories in slang. Along with the description of morphological and semantic features of slang, the differences in slang usage in different countries of the British Isles, where British English is spoken, are described. The practical part analyses the word formation and semantic categories in the slang of British fiction literature of the twentieth and twenty-first centuries. This work aims to view slang as a way to render English speech realistic, depict a social class, or highlight the differences among social classes in the representations of modern and postmodern British literature.

Бакалаврська робота присвячена сленгу як лінгвістичному явищу в британській англійській мові. Вона спрямована на наголошення важливості вивчення варіацій англійської мови та її нестандартних форм. Робота складається з двох частин. В першій частині подані визначення та особливості сленгу. Оскільки сленг не був достатньо дослідженим, а також через плинність сленгу, він залишається одним з найбільш неясних лінгвістичних явищ. Більше того, сленг часто вважають не вартим уваги лінгвістів, оскільки він складає нижній шар лексикону і часто проявляється у формі лайок і образливої або розмовної мови. Дана робота ілюструє, що розуміння сленгу потрібно переосмислити та описати з інших точок зору. Незважаючи на його належність до нижнього шару лексики, сленг характеризується творчістю, грайливістю, та повстанням проти звичаїв. У цій праці також зроблено спробу показати, що сленг може представляти регіональні особливості британської англійської, які теж є частиною цієї мови. Окрім наведення визначення та опису сленгу, теоретична частина також описує основні типи утворення та семантичні категорії сленгу. Разом з описом морфологічних та семантичних характеристик сленгу, також описані морфологічні та семантичні категорії сленгу. У практичній частині аналізуються словотворення та семантичні категорії сленгу, подані в британській художній літературі двадцятого та двадцять першого століття. Ця праця спрямована на бачення сленгу як засіб передати реалістичність опису, зобразити соціальний клас, та підкреслити відмінності між соціальними класами, зображені в модерністській та постмодерністській британській літературі.
Keywords: slang; British English; regional slang; word formation; semantics; сленг; британська англійська мова; регіональний сленг; словотворення; семантика